2003
DOI: 10.1007/s00213-002-1351-4
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for cocaine- or pup-associated chambers differentiates otherwise behaviorally identical postpartum maternal rats

Abstract: Rationale and objectives-Our previous work uncovered a differential preference of maternal female rats for cues associated with pups versus cues associated with cocaine at three different postpartum time points. Our current study examines the preference for these cues in conjunction with an assessment of the capacity to express the maternal behavior at one of these time points. We examined dams at day 10 postpartum using a procedure that included two additional controls, and a complete assessment of the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 58 publications
(53 reference statements)
1
73
0
1
Order By: Relevance
“…The stability of the values is remarkable considering that they are taken from day 4 to day 24 postpartum when the females have very different levels of circulating hormones. Therefore, the marked differences in the reward salience of cocaine across the postpartum period that we have uncovered with our place preference conditioning paradigm (Mattson et al, 2001(Mattson et al, , 2003Wansaw et al, 2003bWansaw et al, , 2004 are not likely due to differences in the peripheral processing or general accessibility of cocaine to the brain to activate motor systems. Hence, we next will investigate whether the differences in the reward salience of cocaine across the postpartum period are likely to be due to changes in the effect of cocaine on specific neural structures that mediate the perception and prioritization of rewards (Mattson and Morrell, in press;Morrell et al, 2005).…”
Section: Plasma Cocaine Levels Metabolite Levels and Locomotor Effementioning
confidence: 79%
See 4 more Smart Citations
“…The stability of the values is remarkable considering that they are taken from day 4 to day 24 postpartum when the females have very different levels of circulating hormones. Therefore, the marked differences in the reward salience of cocaine across the postpartum period that we have uncovered with our place preference conditioning paradigm (Mattson et al, 2001(Mattson et al, , 2003Wansaw et al, 2003bWansaw et al, , 2004 are not likely due to differences in the peripheral processing or general accessibility of cocaine to the brain to activate motor systems. Hence, we next will investigate whether the differences in the reward salience of cocaine across the postpartum period are likely to be due to changes in the effect of cocaine on specific neural structures that mediate the perception and prioritization of rewards (Mattson and Morrell, in press;Morrell et al, 2005).…”
Section: Plasma Cocaine Levels Metabolite Levels and Locomotor Effementioning
confidence: 79%
“…In our original work on the topic, we have shown that middle and late postpartum females prefer cocaine-associated cues, whereas early postpartum females prefer pup-associated cues (Mattson et al, 2001(Mattson et al, , 2003. In our subsequent work we have examined the salience of two hours of conditioning with subcutaneously injected cocaine (versus saline) independent of the pup-associated cues.…”
Section: Overall Conclusionmentioning
confidence: 99%
See 3 more Smart Citations